2010
DOI: 10.1175/2009jpo4264.1
|View full text |Cite
|
Sign up to set email alerts
|

Thermocline Circulation in the Solomon Sea: A Modeling Study*

Abstract: In the southwest Pacific, thermocline waters connecting the tropics to the equator via western boundary currents (WBCs) transit through the Solomon Sea. Despite its importance in feeding the Equatorial Undercurrent (EUC) and its related potential influence on the low-frequency modulation of ENSO, the circulation inside the Solomon Sea is poorly documented. A 1 /128 model has been implemented to analyze the mean and the seasonal variability of the Solomon Sea thermocline circulation. The circulation involves an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
91
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(108 citation statements)
references
References 46 publications
15
91
2
Order By: Relevance
“…The highest level of variability, up to 16 cm rms, was quite localized in front of the Solomon Strait. High variability is in accordance with complex current recirculation that developed in the model for this area (Melet et al 2010). The western and eastern Solomon Sea SLA signals are highly correlated (0.91 correlation) with their variability that varies from 5.6 to 10.4 cm rms, respectively.…”
Section: Overall Descriptionsupporting
confidence: 70%
See 2 more Smart Citations
“…The highest level of variability, up to 16 cm rms, was quite localized in front of the Solomon Strait. High variability is in accordance with complex current recirculation that developed in the model for this area (Melet et al 2010). The western and eastern Solomon Sea SLA signals are highly correlated (0.91 correlation) with their variability that varies from 5.6 to 10.4 cm rms, respectively.…”
Section: Overall Descriptionsupporting
confidence: 70%
“…The 1/12°resolution model used in this study is described in detail in Melet et al (2010). Therefore, only a brief description is provided here.…”
Section: Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In a second step, the increase in resolution is achieved by setting up a 1/36° AGRIF nest (dedicated section in the following) over the Solomon Sea in the intermediate model. This two steps embedding strategy, comparable to that used at coarser resolution by Melet et al 3 but only briefly mentioned in their paper, is motivated by the need to preserve the upscaling effects of the 1/36° Solomon Sea on a greater area of the southwest Pacific and still not to carry on computations with the whole 1/12° global model. In the perspective of operational use, the use of the intermediate one-way embedment of an intermediate model in a global model at the same resolution (1/12°) has several advantages.…”
Section: Model Strategymentioning
confidence: 99%
“…In the Solomon Sea, Melet et al 3 have shown that the circulation is notably constrained by the narrowness of Vitiaz Strait, which is partly responsible for a splitting of the main western boundary current into two branches upstream of the strait. Therefore, an accurate representation of the bathymetry is essential to correctly model the Solomon Sea circulation.…”
Section: Bathymetrymentioning
confidence: 99%